Production model to increase productivity and delivery compliance in the peruvian textile sector by applying value stream mapping, 5s and flexible production systems - Barzola-Cisneros, Víctor (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.